Spot-flanked Gallinule Porphyriops melanops (Aves: Rallidae) feeding biology in the Middle Parana River flood-plain, Argentina - F. Olguin, Pamela (Universidad Antonio Nariño, 2021)
A proposal for sustainable usage of rails population should take into account complete alimentary requirements. Hence, the purpose of the following study was to determine the feeding biology of the Spot-flanked Gallinule Porphyriops melanops. The research was conducted on 11 stomach contents to find out trophic diversity by stomach (H), accumulated trophic diversity (Hk), Relative Importance Index (IRI), alimentary efficiency, prey size percentage and intestinal coefficient (Ri). The resultant spectrum was composed by 10 taxonomical entities, 7 animal fractions and 3 vegetable fractions; trophic diversity by stomach (H) ranged between 0 and 1, while accumulated trophic diversity (Hk) was 2,57; main IRI values were as follows: Polygonum accuminatum 1204, Planorbidae 872 and Paspalum repens 451; alimentary efficiency was 97,5%; more frequent prey sizes oscillated between 0 and 10 mm; habitat preference was 2,4; and the average intestinal coefficient was 2,79.